2010
DOI: 10.1111/j.1365-2842.2010.02179.x
|View full text |Cite
|
Sign up to set email alerts
|

Objective and subjective assessment of masticatory function for patients with temporomandibular disorder in Korea

Abstract: This study examined the differences in the masticatory function of patients with temporomandibular disorder (TMD) in Korea. The experimental groups were as follows: 23 patients with painful arthralgia classified as pain group according to the research diagnostic criteria for temporomandibular disorder (RDC/TMC) and 28 patients with pain-free disc displacement and reduction classified as clicking group. The subjects were obtained from those who had visited Yonsei University Dental Hospital from 2007 to 2008. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
1
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 31 publications
5
17
1
10
Order By: Relevance
“…The correlation coefficients between the maximum bite force, the MAI and the FIA in this study were in agreement with other studies, which reported moderate correlations between the subjective FIA and the objective MAI , and between the FIA and the maximum bite force .…”
Section: Discussionsupporting
confidence: 93%
“…The correlation coefficients between the maximum bite force, the MAI and the FIA in this study were in agreement with other studies, which reported moderate correlations between the subjective FIA and the objective MAI , and between the FIA and the maximum bite force .…”
Section: Discussionsupporting
confidence: 93%
“…However, measuring PD and clinical attachment level using a periodontal probe and assessing gingival inflammation by various indices are still the most reliable methods for diagnosing periodontal disease. In medicine and dentistry, some efforts have been made to measure the presence, severity, and risk of developing diseases, such as chronic inflammatory disease, alcohol abuse and dependence, and masticatory dysfunction, by using objective or subjective evaluation methods 33‐35 . These methods measure physical function, behavior, and mental problems by evaluating the physical or biologic factors or by using questions about behavior, habits, and awareness of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported significant correlations between objective signs and subjective symptoms of TMD (Kim et al , 2010; Ahn et al , 2011). However, the present study revealed that objective signs were not significantly correlated with subjective symptoms in TMD patients with psychological problems.…”
Section: Discussionmentioning
confidence: 94%